Effect of Addition of Thyroxine in the Treatment of Graves’ Disease: A Systematic Review - Li, Jun; Bai, Litao; Wei, Fan; Wei, Maoying; Xiao, Yao; Yan, Weitian; Wei, Junping (Frontiers in Endocrinology, 2021)
Graves' disease is the most common cause of hyperthyroidism. Antithyroid drugs, radioiodine ablation, and surgery are the principal treatments. Since research has pointed out that adding thyroxine to antithyroid therapy can improve the therapeutic effect, many similar studies have been conducted subsequently. The purpose of this study was to investigate whether adding thyroid hormone to various treatments for Graves' disease has clinical benefit. A total of 27 articles was included, and the risk of research bias was moderate to high. We divided the discussion into three categories, including remission and relapse rates, non-drug treatment, and other effects. Overall, the available evidence does not support the indiscriminate supplements of thyroxine to various treatments for Graves 'disease, especially in combination with oral thyroid drugs. Further clinical studies are required to explore the adaptation of thyroxine addition in the treatment of Graves' disease.